Comparison of morphology and mechanical properties of peroxide‐cured acrylonitrile butadiene rubber/LDH composites prepared from different organically modified LDHs. Issue 5 (19th May 2012) - Feng, Jianxiang; Liao, Zedong; Zhu, Jin; Su, Shengpei
Abstract Rubber compounds based on acrylonitrile butadiene rubber (NBR) containing organically modified layered double hydroxides (LDHs) were prepared using peroxide as a curing agent. The LDHs intercalated by organic compounds including sodium styrene sulfonate (SSS) and sodium dodecylbenzene sulfonate (SDBS) were investigated using thermogravimetric analysis (TGA) and X‐ray diffraction (XRD) while the unmodified LDHs were used as contrast. Experimental results from TGA and XRD showed that both SSS‐ and SDBS‐intercalated LDHs were successfully obtained. The morphology of the LDH composites was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and XRD. The chemical structure of NBR/LDHs compounds were measured by Fourier transform infrared spectrum. The thermal properties were measured by TGA and differential scanning calorimetry. Other properties such as mechanical and swelling properties were also investigated. The results showed that a chemical bonding between organically modified LDHs and rubber matrix through SSS was built during vulcanization, which leads to improved interfacial strength of the cured compound. A high‐performance acrylonitrile butadiene rubber/SSS‐modified LDH compound, which has two times higher tensile strength than cured pure rubber without significant loss of elongation, was obtained. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013